Implementasi Layanan Puspaga Kota Surabaya Dalam Pendampingan Psikoedukasi Untuk Mewujudkan Ketahanan Keluarga Di Tengah Arus Modernisasi - Dita Anggraini; Berliana Mustika Rani Berliana (CV. Ulil Albab Corp, 2026)
Modernization presents challenges to family harmony, parenting patterns, and intergenerational communication, which can potentially lead to dysfunction in family dynamics. To address this, the Surabaya City Government has established the Family Learning Center (PUSPAGA) as a preventive service providing consultation, education, and mentoring. This article describes the implementation of PUSPAGA using a descriptive qualitative approach, based on literature studies and the author's field observations. Through services such as family counseling, parenting classes, pre-marital classes, and socialization programs, PUSPAGA provides effective psychoeducation in helping parents understand positive parenting, strengthening family communication, and preventing potential household conflicts.